The mythical world of Atlantis theories of the lost empire from Plato to Disney - Kurtti, Jeff; Whitmore, Preston B. (Disney Editions, 2001)
This comprehensive study of the famed lost empire contains elements of theories of Atlantis put forth by philosophers and historians alongside the theory revealed in Disney's new animated feature.